Assessing nursing information competence of nurses and identifying the associated influencing factors - Li, Yun-xia; Fan, Xiao-wen; Huang, Chen; Pan, Hong-ying (Frontiers in Medicine, 2025)
PurposeThe objective of this study was to assess the level of nursing information competence (including computer competence, information competence, and comprehensive application competence dimensions) of nurses and determine the influencing factors related to nursing information competence.BackgroundThe wide application of information technology in medical system can improve the quality of nursing service. At present, the evaluation results of nurses’ informatics competence are not consistent.MethodsThis cross-sectional study survey was carried out in a tertiary hospital in Zhejiang, China, November 3 to November 9, 2023. Nurses who meet the inclusion and exclusion criteria were recruited through purposive sampling method.ResultsThis study involved 1,237 nurses. The median score of nurses’ informatics competence of 1,237 nurses was 98 (83,110), and the median score for each item was 2.88 (2.44, 3.24). The nursing information competence score were divided into three groups: high group (358, 28.94%), medium group (598, 48.34%), and low group (281, 22.72%), with score of 94 (interquartile range: 15), 71 (interquartile range: 14), 49 (interquartile range: 19). Eight variables strongly correlated with the total nursing information competence score were identified: (1) ability to adopt corresponding educational methods to disseminate information technology knowledge; (2) ability to effectively use clinical information according to work needs; (3) ability to evaluate the quantity and quality of information resources and adjust search strategies as needed to further obtain information; (4) ability to combine quality management tools to analyze and apply information; (5) ability to regularly collate medical record data using information systems and classify them by different purposes; (6) ability to select search strategies and effectively obtain information from the internet or electronic databases; (7) ability to clearly express problems encountered in information technology use; (8) familiarity with commonly used network terms. The prediction accuracy of Gradient Boosting regression and Linear regression models reached 0.829 and 0.836, respectively.ConclusionThis study shows that the informatics competence score of nursing staff is in the middle to upper level, and hospital managers can carry out more targeted and personalized training in the aforementioned 8 aspects.